The Impact of Advertising Appeal, Celebrity Endorsement and Repetition Advertising in Television Advertisement Toward Purchase Intention OPPO Smartphone - Laras Aprilita Priatna (Prosiding Industrial Research Workshop and National Seminar, 2018)
This research purposes to: 1) investigate the impact of advertising appeal, celebrity endorsement and advertisingrepetition on purchase intention OPPO smartphone, 2) identifying the factors that most impact on purchaseintention OPPO Smartphone and the research population is all people who have been watching oppo smartphoneadvertisement in television with a sample of 470 respondents in Bandung. The sample was taken using judgmentsampling. The methods used in analyzing the data are using validity and reliability test, and multiple regressionanalysis. The result of this research show that Advertising have a significantly impact on purchase intention, andthe most influence factor is advertising repetition.